Non-erosive gastroesophageal reflux disease determination criteria by functional tests: a predictive model based on multivariate analysis - Aponte, Raúl; Daulabani, Nefertiti; de Jesús, Zuleyma; Rengifo, Soberanía; Pérez-Ybarra, Luis (International Journal Of Community Medicine And Public Health, 2021)
Background: Gastroesophageal reflux disease (GERD) in 2009 presented a prevalence of 11.5% in Venezuela. It is a complex, multifactorial disease that is difficult to define, since it consists of several signs and symptoms that may or may not coexist together, both in the presence and absence of the disease. Methods: A prospective study was conducted that consisted of a group of 85 patients diagnosed with non-erosive gastroesophageal reflux disease (NERD) and 20 asymptomatic volunteers. Functional tests were conducted on both groups that included high resolution manometry, 24-hour pH-metry - impedance study. The chi-square independence test, principal component analysis and multiple correspondence analysis were applied to identify which variables showed greater association and importance for the diagnosis of NERD. Results: The results indicated that it is possible to establish a rapid diagnostic test based on the solid drink test, distal contraction index, peristaltic jumps and presence of heartburn with a sensitivity of 96% and specificity of 90%. Conclusions: It is possible to establish a NERD rapid diagnostic test based on functional tests.